Modern society: new challenges and risks - Danilov, Alexander N.; Bezniuk, Dmitry K.; Bogdevich, Iosif M.; Vodopiyanov, Pavel A.; Volotovsky, Igor D.; Zelenkov, Anatoly I.; Mamedov, Agamali K.; Mojeiko, Marina A.; Rubanau, Anatoly V.; Titarenko, Larissa G.; Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2022)
The round table is devoted to the discussion on a wide range of problems related to new challenges and prospects for the development of modern society. These are the challenges of global instability, bio- and cybersecurity, pandemic problems, digitalisation, which all lead the world to large-scale crises: economic, environmental, anthropological, etc. In the conditions of global instability, there is a rise of connections and interactions that fix new social changes, some other integrity, and the crisis of the technogenic civilisation. In this case, modernity is perceived not as a completed project, but as a process of updating social reality, a person’s ideas about society. It includes the main aspects of human relations to the world, and opens up a great civilisational diversity, which only grows with time. The catalysts of change on the way to a new modernity are values that reflect changes in life meanings under the influence of social life. Constantly emerging new risks and challenges motivate the reset of values that are tested in the depths of culture and only after that become ideals for imitation and reproduction. Currently, there is another change of milestones. Modernity imposes its own requirements on the processes taking place in society, and largely determines the course of global evolution as the path of ascent of complex systems to higher levels of organisation and complexity.
Keywords: modern society; new challenges and risks; social changes; sociology of life; crisis of technogenic civilisation; cellular paradigm; ecological carelessness; interdisciplinary synthesis; life world; language of modern sociology